Transient resonant Auger–Meitner spectra of photoexcited thymine. (10th February 2021) - Wolf, Thomas J. A.; Paul, Alexander C.; Folkestad, Sarai D.; Myhre, Rolf H.; Cryan, James P.; Berrah, Nora; Bucksbaum, Phil H.; Coriani, Sonia; Coslovich, Giacomo; Feifel, Raimund; Martinez, Todd J.; Moeller, Stefan P.; et al.
Abstract : We present the first investigation of excited state dynamics by resonant Auger–Meitner spectroscopy (also known as resonant Auger spectroscopy) using the nucleobase thymine as an example. Abstract : We present the first investigation of excited state dynamics by resonant Auger–Meitner spectroscopy (also known as resonant Auger spectroscopy) using the nucleobase thymine as an example. Thymine is photoexcited in the UV and probed with X-ray photon energies at and below the oxygen K-edge. After initial photoexcitation to a ππ* excited state, thymine is known to undergo internal conversion to an nπ* excited state with a strong resonance at the oxygen K-edge, red-shifted from the ground state π* resonances of thymine (see our previous study Wolf, et al., Nat. Commun., 2017, 8, 29). We resolve and compare the Auger–Meitner electron spectra associated both with the excited state and ground state resonances, and distinguish participator and spectator decay contributions. Furthermore, we observe simultaneously with the decay of the nπ* state signatures the appearance of additional resonant Auger–Meitner contributions at photon energies between the nπ* state and the ground state resonances. We assign these contributions to population transfer from the nπ* state to a ππ* triplet state via intersystem crossing on the picosecond timescale based on simulations of the X-ray absorption spectra in the vibrationally hot triplet state. Moreover, we identify signatures from the initially excited ππ* singlet state which we have not observed in our previous study.